The Causes of Acute Fever Requiring Hospitalization in Geriatric Patients: Comparison of Infectious and NoninfectiousEtiology - A. Atahan Cagatay; Fatih Tufan; Fehmi Hindilerden; Sibel Aydin; Omer Celal Elcioglu; Asli Karadeniz; Nilufer Alpay; Suut Gokturk; Ozer Taranoglu (Journal of Aging Research)
Introduction. Infectious diseases may present with atypical presentations in the geriatric patients. While fever is an important finding of infections, it may also be a sign of noninfectious etiology. Methods. Geriatric patients who were hospitalized for acute fever in our infectious diseases unit were included. Acute fever was defined as presentation within the first week of fever above 37.3∘C. Results. 185 patients were included (82 males and 103 females). Mean age was 69.7±7.5 years. The cause of fever was an infectious disease in 135 and noninfectious disease in 32 and unknown in 18 of the patients. The most common infectious etiologies were respiratory tract infections (𝑛=46), urinary tract infections (𝑛=26), and skin and soft tissue infections (𝑛=23). Noninfectious causes of fever were rheumatic diseases (𝑛=8), solid tumors (𝑛=7), hematological diseases (𝑛=10), and vasculitis (𝑛=7). A noninfectious cause of fever was present in one patient with no underlying diseases and in 31 of 130 patients with underlying diseases. Conclusion. Geriatric patients with no underlying diseases generally had infectious causes of fever while noninfectious causes were responsible from fever in an important proportion of patients with underlying diseases.